Resilience and adaptability of tourism in EaP region: A systematic literature review - Irina Manolescu; Mihai Talmaciu (CES Working Papers, 2021)
Tourism in the Eastern Partnership countries experienced a sinuous evolution in the post-Soviet period. The abandonment of the classic circuits, economic stagnation, the shock suffered after the events and periods of political crisis, and lately, the frozen activity during the health crisis, make resilience a way of being of the actors in this field. The paper aims at a systematic analysis of studies targeting the forms of tourism in the Eastern Partnership countries, highlighting the development models followed, the areas of tourist concentration and the recommended strategies. From a methodological point of view, the research was staged, having an initial quantitative approach, and then a qualitative one - a content analysis highlighting the key guidelines of the analysed studies. The conclusions of the article aim at mapping the research areas covered by the articles studied, while highlighting the intensely frequented areas and the "white" areas.
Keywords: 330; literature review; tourism; resilience; post-soviet space